Creating and sustainable development of specialized centers as a way to improve quality of medical care - V. I. Guzeva; O. V. Guzeva; V. V. Guzeva; D. O. Dukhanina; V. R. Kasumov (Бюллетень сибирской медицины)
Quality of care is evaluated on the completeness of the survey, the correct diagnosis, treatment efficacy, and its duration. Improving the quality and efficiency of medical care for children with paroxysmal disorders of consciousness is one of topical problems of neurology.Aim. The aim of the work is to justify the relationship between improving the quality of health care and sustainable development in the modern conditions of specialized medical centers on the example of the work on the identification and treatment of children with paroxysmal disorders of consciousness of the Center for diagnosis and treatment of epilepsy, and sleep disorders in children and adolescents at the department neurology, neurosurgery and medical genetics SPbGPMU.Materials and methods. For more accurate diagnosis and treatment at the Center conducted a comprehensive examination, including video-EEG оf 527 children aged 1 month to 18 years. A clinical trial study included medical cases, assessment of neurological and somatic status, the study of seizure types and forms of the disease. Instrumental methods of examination were determined by EEG and MRI studies of the brain.Main results. Comprehensive survey of sick children with monitoring video-EEG revealed that 317 children (60,1%) had epileptic paroxysms and 210 children (39,8%) – non-epileptic paroxysms. Correction treatment was performed in 284 (89,5%) children with epileptic paroxysms and altered the treatment in 190 (90,4%) children with epileptic paroxysms.Conclusion. The presented clinical data show the high effectiveness of the Centre in the diagnosis and treatment of children with paroxysmal disorders of consciousness. The accumulated experience in the Center confirms the relevance of the creation of the structure of scientific and educational institutions specialized centers in which patients will be given to high-quality medical care.